Analysis Of Passive Heat Removal Systém Trough Steam Generator By Ansoft Fluent - Petrosyan, Taron (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
This paper presents the simulation of the condensation of water vapor in one tube of the heat exchanger in the Passive Heat Removal System, which is a protective safety system of the Nuclear Power Plant. The simulation accounts for the turbulent flow of the gas along the tube with an assumption of constant wall temperature. The results from the CFD (computational fluid dynamics) simulations are compared with the experimental results from the literature for the condensation of water vapor and in general, agree well.
Keywords: PHRS; CFD; ANSYS; Fluent; thermal-hydraulics; NPP